Estimasi Elastisitas Pendapatan pada Komoditas Energi di Indonesia - Asyahid, Esa Azali (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to estimate the income elasticity of household electricity demand in Indonesia. Household sector represents the largest electricity user and the main recipient of energy subsidies in the country. The study employs micro panel data from the fourth and fifth waves of the Indonesian Family Life Survey (IFLS), covering more than 27,000 households. The analysis is conducted using a panel regression model with the fixed-effects method to control for unobserved individual heterogeneity. The main variables used include monthly electricity expenditure as a proxy for energy consumption and total household expenditure as a proxy for income. The estimation results indicate that the income elasticity of household electricity consumption is 0.63 and statistically significant, suggesting that electricity is a normal good as well as a basic necessity. Further analysis reveals that income elasticity in urban areas is slightly higher than in rural areas. Moreover, the higher the household’s economic status, the lower its income elasticity, ranging from 1.05 in the lowest income quartile to 0.44 in the highest quartile.